The effects of 8 weeks of integrative neuromuscular pitch training on strength values and sprint performance in young élite soccer players - Italo, S.; Giacomo, C.; Rosario, D. O. (Journal of Physical Education and Sport, 2023)
Introduction.Youth soccer imposes a series of high-intensity movements that require adequate levels of explosive strength from the earliest categories of competition.The organization of training sessions is a very timely issue in youth soccer because it requires careful analysis of modulating loads and managing the duration of training sessions. For these reasons, the following should be sought: a) effective organizational solutions for training the young player, and b) drills and loads that can meet the time allocated to training sessions. Purpose.The purpose of the study is to analyse and understand the effects of integrative neuromuscular pitch training on strength values and sprint performances in the young soccer players. Materials and methods.37 young male soccer players (all movement players) from youth national team in the 2020/21 season (14.31 ± 0.64 years, weight: 48.96± 6.72 kg; height: 161.1± 9.2 cm, age training: 8,1 ± 1,2 years) have been randomly divided into Experimental Group, EG (n=17) and Control Group, CG (n=20). The EG completed a total of 16 training sessions directed at neuromuscular training on the pitch: two 30-minute sessions/week over a 8-week period. The CG followed an identical training schedule, but training sessions consisted of soccer-specific drills only. The performances were assessed in the One-Leg Hop test, Side-Hop test, CounterMovement Jump (CMJ),10 metres sprint test and 20 metres sprint test. Results.The data analysis returns the highlights significant intergroup results (T0 vs T1): the One-Leg Hop test left limb (p = .05, d = -2,67), the Side test left (p= .0005, d= -6.40) and right limb (p= .0005, d= 5.32), the CMJ test ((p= .0005, d= -6.96), the 10 metres sprint test (p= .001, d= -2.04) and the 20 metres sprint test (p= .001, d= -2.25). Conclusions.The integrative neuromuscular pitch training seem to respond effectively to two needs of the young soccer player: the lower limb strength values increase and the sprint performance increase.